Improved Release of a Drug with Poor Water Solubility by Using Electrospun Water-Soluble Polymers as Carriers - Muriel Józó; Nóra Simon; Lan Yi; János Móczó; Béla Pukánszky (MDPI AG, 2021)
In an attempt to improve the solubility of valsartan, a BCS II drug, fibers containing the drug were prepared from three water-soluble polymers, hydroxypropyl-methyl-cellulose (HPMC), polyvinyl-pyrrolidone (PVP), and polyvinyl-alcohol (PVA). Fiber spinning technology was optimized for each polymer separately. The polymers contained 20 wt% of the active component. The drug was homogenously distributed within the fibers in the amorphous form. The presence of the drug interfered with the spinning process only slightly, the diameters of the fibers were in the same range as without the drug for the HPMC and the PVA fibers, while it doubled in PVP. The incorporation of the drug into the fibers increased its solubility in all cases compared to that of the neat drug. The solubility of the drug itself depends very much on pH and this sensitivity remained the same in the HPMC and PVP fibers; the release of the drug is dominated by the dissolution behavior of valsartan itself. On the other hand, solubility and the rate of release were practically independent of pH in the PVA fibers. The different behavior is explained by the rate of the dissolution of the respective polymer, which is larger for HPMC and PVP, and smaller for PVA than the dissolution rate of the drug. The larger extent of release compared to neat valsartan can be explained by the lack of crystallinity of the drug, its better dispersion, and the larger surface area of the fibers. Considering all facts, the preparation of electrospun devices from valsartan and water-soluble polymers is beneficial, and the use of PVA is more advantageous than that of the other two polymers.